2mn/4m^4n^-3

Thank you for the opportunity to help you with your question!

= mn /2 m^4n^-3

= m *m^ -4 * n / 2 n^-3 ( because 1 / m^4 = m^ -4)

= m^(1+ -4) * n / 2 n^-3 (because m^ 1 * m^-4 = m^(1+ -4)

= m^(-3) * n / 2 n^-3

= m^(-3) * n *n^ 3 / 2 ( because 1 / n^ -3= n^ 3)

= m^(-3) * n ^(1+ 3 ) / 2 (because n*n^3 = n^(1+3)

= m^-3 * n ^ 4 / 2 .........................................ANSWER

= n ^ 4 / 2 m^3 .........................................ANSWER

answers are

= m^-3 * n ^ 4 / 2

both are same ...you can select the answer from your choices

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up